DAMPAK KECELAKAAN LALU LINTAS DALAM KARYA SENI LUKIS - RODHANIL WAN JOHAR, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2019)
The purpose of the creation of this final work is to visualize the impact of traffic accidents on contemporary painting and to remind people of driving to pay more attention to the safety of themselves and others.The method of creating this final work uses five stages, namely the preparation stage, the elaboration stage, the synthesis stage, the concept realization stage and the completion stage, and the latter holds an exhibition of painting works using acrylic paint media and oil paint on canvas using brush strokes and using color that matches the object, using contemporary patterns. Ten works that were raised told about what made the accident happen. Because many road users in Indonesia are indifferent and do not obey the rules and be selfish. The behavior of non-traffic discipline is still widely found in the community, as has been manifested in contemporary painting with the procedure of traffic that is not properly lived in social life.Kata kunci: Kecelakaan Lalu Lintas, Seni Lukis